The mathematical communication ability based on gender difference on students of 11th grade by using problem-based learning model assisted by probing prompting technique - Zakiri, Ishmah Khairina; Pujiastuti, Emi; Asih, Tri Sri Noor (Unnes Journal of Mathematics Education, 2018)
This study aims to test the MCA (Mathematical Communication Ability) in Problem Based Learning (PBL) model assisted Probing Prompting Technique (PBL PP), to achieve learning mastery, to know the average ratio of MCA of students on learning model of PBL PP and PBL only, to differ the MCA of male students with female students in PBL PP, and to describe MCA of students based on gender difference. The method used in this research is mix method. While the population is science program students of XI grade at MAN 2 Semarang. The sample is chosen with random sampling. In addition, students of XI IPA 1 are as experiment class, while students of XI IPA 2 as control class. The qualitative research subjects in this study are six students, for each is taken three from every male and female students in experiment class. The results of this research are the MCA’s students with PBL PP learning reaches the learning mastery, the average ratio of MCA in PBL PP is better than PBL model, the MCA of male and female students have no significant difference, and there are some differences of MCA in each indicators based on gender difference.